Pengaruh Kepemimpinan Pelayanan dan Komitmen Organisasi Terhadap Kinerja Kerja - Sutisna, Ade Jaya; Noor, Juliansyah (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
This study purpose to examine servant leadership (SL) influence on job performance (JP) and to examine the organizational commitment (OC) role as a mediator. Data were collected from 230 employees of Insurance firms in Banten province, Indonesia employing a 15-item questionary. In total, 220 questionnaires were reverted, outcome in a reply rate of 95 percent. The model of mediating was analyzed and tested employing structural equation modeling (SEM) with Partial Least Square (PLS)3.3.2. The finds indicated that SL had a positive between OC and JP confirming the OC role as a mediator. This result shows that managers are able to increase OC and JP by employing an SL style. Furthermore, the managerial fundamentals resulted from this finding must be considered a solution for increasing JP. The contribution of this results in the JP concept by giving a reasonable explanation of OC's role as a mediator in relating SL to JP Keywords: job performance, servant leadership, organizational commitment, Banten, SEM